Formulation design, in vitro evaluation and stability studies on mucoadhesive buccal films of anti-anginal calcium channel blocker - Bharath Kumar.V, Ashok kumar.A, Sudheer.B, Suresh Kumar.K, Srinivasa Rao.V, Kirtinidhi.K, Hitesh R Patel, Putta Rajesh Kumar (Journal of Applied Pharmaceutical Science)
Diltiazem hydrochloride has poor oral bioavailability, easily undergo first passage effect in the liver. Hence, an attempt was made to prepare and evaluate mucoadhesive buccal films containing diltiazem hydrochloride by employing HPMC, eudragit, ethyl cellulose alone and in combination with PVP. The I.R and DSC studies showed that there was no interaction between drug and the utilized polymer. The prepared mucoadhesive buccal films showed uniform thickness, weight, folding endurance, surface pH, drug content and swelling index. The drug content of all the formulation was found to be uniform. In vitro drug release studies indicated that the films prepared with HPMC (3%) and ethyl cellulose (4%) has shown fast and slow release respectively. The formulations incorporated with SLS and sodium glycocholate indicated significant drug release from F11 and F15. Later the in-situ diffusion studies using goat cheek pouch showed faster drug release from film with 1% (SLS). About 93.04% and 91.83% of drug release profile were observed during in situ diffusion studies at the end of 9hrs and 18 hrs respectively. The formulated films were stable during stability studies at 45ºC and 75%RH with respect to drug content.
Keywords: Diltiazem hydrochloride, HPMC, Eudragit, Ethyl cellulose, Permeation enhancers and In situ diffusion studies.